Combined Effect of Low and High Rate of Corrugated Steel Fiber and Stirrups on Mechanical Performance of SFSCC Beams - Lassoued, Rachid; Chaib*, Sihem (Graduate School of Universitas Syiah Kuala, 2021)
To improve the fragile nature of concrete, its low tensile strength, and a view to giving it the desired properties, which serve to build more durable structures at less cost, the association of a self-consolidating concrete with fiber, is considered a wise combination. However, given the limited amount of research on the response of SFSCC structures, designers and engineers do not use this material with confidence. In the present work, an experimental companion was conducted to examine the combined effect of fibers and stirrups, including the low and high rate of steel fiber, on the behavior of SFSCC beams. This choice allowed working on economically viable SFSCC. Beams were also madewith ordinary concrete and others with self-consolidating. Thirty-six beams were of identical cross-section 10x20cm and length of 120cm; carried out with or without longitudinal and transverse reinforcement. Before proceeding with the main part of the research program, the concrete mixtures were characterized first in the fresh state by the following tests: Slump Flow, Time Flow T500; J-Ring, L-Box, V-Funnel, and Sieve stability, and then in the hardened state: compressive and tensile strengths. In the light of the results obtained, it was found that adding steel fibers to fresh self-consolidating concrete decreased its workability and fluidity but improved its hardening properties. Subsequently, the addition of the steel fibers increased the flexural capacity of the beams significantly and enhanced their ductility. Also, an addition of the steel fibers in an adequate percentage, in this case at 0.90%, made it possible to replace the shear reinforcements and can lead to changing the mode of failure from a collapse by brittle shear to a mechanism of ruin in ductile bending.